Theoretical and Experimental Insight into the Mechanism for Spontaneous Vertical Growth of ReS2 Nanosheets. (28th May 2018) - Ghoshal, Debjit; Yoshimura, Anthony; Gupta, Tushar; House, Andrew; Basu, Swastik; Chen, Yanwen; Wang, Tianmeng; Yang, Yang; Shou, Wenjia; Hachtel, Jordan A.; Idrobo, Juan Carlos; Lu, Toh‐Ming; et al.
Abstract: Rhenium disulfide (ReS2 ) differs fundamentally from other group‐VI transition metal dichalcogenides (TMDs) due to its low structural symmetry, which results in its optical and electrical anisotropy. Although vertical growth is observed in some TMDs under special growth conditions, vertical growth in ReS2 is very different in that it is highly spontaneous and substrate‐independent. In this study, the mechanism that underpins the thermodynamically favorable vertical growth mode of ReS2 is uncovered. It is found that the governing mechanism for ReS2 growth involves two distinct stages. In the first stage, ReS2 grows parallel to the growth substrate, consistent with conventional TMD growth. However, subsequent vertical growth is nucleated at points on the lattice where Re atoms are "pinched" together. At such sites, an additional Re atom binds with the cluster of pinched Re atoms, leaving an under‐coordinated S atom protruding out of the ReS2 plane. This under‐coordinated S is "reactive" and binds to free Re and S atoms, initiating growth in a direction perpendicular to the ReS2 surface. The utility of such vertical ReS2 arrays in applications where high surface‐to‐volume ratio and electric‐field enhancement are essential, such as surface enhanced Raman spectroscopy, field emission, and solar‐based disinfection of bacteria, is demonstrated. Abstract : This study uncovers the mechanism that underpins the thermodynamically favorable out‐of‐plane growth of ReS2 nanosheets. It is reported that ReS2 growth initiates parallel to the substrate, but later vertical ReS2 sheets nucleate and grow from specific "seed" points. It is explained why it is thermodynamically favorable for ReS2 to grow out‐of‐plane and why similar effects are not observed in conventional group‐VI transition metal dichalcogenides.